2021
DOI: 10.1002/oby.23227
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle energy metabolism in obesity

Abstract: Comparing energy metabolism in human skeletal muscle and primary skeletal muscle cells in obesity, while focusing on glucose and fatty acid metabolism, shows many common changes. Insulin‐mediated glucose uptake in skeletal muscle and primary myotubes is decreased by obesity, whereas differences in basal glucose metabolism are inconsistent among studies. With respect to fatty acid metabolism, there is an increased uptake and storage of fatty acids and a reduced complete lipolysis, suggesting alterations in lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 131 publications
4
31
0
Order By: Relevance
“…Skeletal muscles play an important role in lipid metabolism, while the excessive accumulation of lipids can impair oxidative capacities, promote lipotoxicity and lead to changes in the structure and function of skeletal muscles. 34 As predicted, we discovered changes in genioglossus muscle fibres of HFD mice, with a decrease in the number of muscle fibres and an increase in the collagen content.…”
Section: Discussionsupporting
confidence: 76%
“…Skeletal muscles play an important role in lipid metabolism, while the excessive accumulation of lipids can impair oxidative capacities, promote lipotoxicity and lead to changes in the structure and function of skeletal muscles. 34 As predicted, we discovered changes in genioglossus muscle fibres of HFD mice, with a decrease in the number of muscle fibres and an increase in the collagen content.…”
Section: Discussionsupporting
confidence: 76%
“…However, previously we have found significant reductions in LDL serum concentrations after an 8-week intervention of LOW-HIIT in untrained normal-weight individuals [ 58 ]. Thus, we assume that our LOW-HIIT protocol can evoke positive alterations in blood lipids in metabolically less compromised individuals, while obese MetS patients, who typically display unfavorable metabolism abnormalities (e.g., altered substrate utilization [ 102 ]), may require higher volumes of exercise to achieve significant improvements in cardiometabolic blood markers. In accordance with the literature, showing that increased volume of RT via an increased number of sets has a larger impact on blood lipids [ 103 ], we observed that among the RT modalities, only 3-RT significantly lowered serum triglyceride concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Damaged skeletal muscle reduces myokine production. Much evidence reported that the expression of myokines was decreased in response to energy-deficient states in skeletal muscle [ 31 , 32 , 33 , 34 ]. In particular, skeletal muscle-derived PGC1α, irisin, and CTSB are important for energy homeostasis not only in the peripheral but also centrally via the muscle-brain endocrine loop [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%